THE DISCOURSE OF THE NATIONAL SECURITY STRATEGY OF THE UNITED STATES OF AMERICA AFTER THE COLD WAR - Forca, Božidar (Serbian political thought, 2026)
The paper analyses the United States’ approach to national security after the Cold War. The research is primarily conducted through an analysis of U.S. national security strategy documents from 1991 to 2025. The authors discuss the U.S. national security strategy document in the first part of the paper, as it originated in the United States. The second part of the paper analyses American strategies after the Cold War, from President George H. W. Bush in 1991 to President Joseph Biden in 2022. A special section is devoted to the analysis of the most recent U.S. National Security Strategy, published by the Trump administration in 2025. By applying the comparative method, content analysis, and the case study method, the authors reach the following conclusion: Politics is dominant, because interests rule the world, but strategy answers the question – how? All U.S. national security strategies after the Cold War are directed toward global leadership and/or U.S. hegemony; what differs is the discourse of presidential administrations within them and their conduct in practice.